Is there a theology of rabbinic Judaism? - Neusner, Jacob (Nordisk judaistik, 1995)
What is at stake in the problem of theology? It is whether or not, out of a given body of authoritative writings, we may appeal to that -ism, that "Judaism", that all of us assume forms the matrix for all the documents all together. That is to say, the issue of theology bears consequence because upon the result, in the end, rests the question of whether we may speak of a religion, or only of various documents that intersect here and there. When we ask not merely for a compendium of what a given religion alleges, e.g. about God, the world, and the human person, but for a systematic and philosophical coherent formulation of convictions in a statement that is not only true but also harmonious and genuinely cogent, then our problem in answering the question at hand proves not so readily resolved. The source of confusion lies in the state of the written evidence of religion, Rabbinic Judaism, or the Judaism of the dual Torah, or Classical Judaism, or Normative Judaism, as people may prefer to call it. We do not know what is primary and generative, what is secondary and derivative. Hence we have theological statements but no clear system. But to maintain there is a theology of Rabbinic Judaism is to claim for the matter systemic, not merely random and notional, standing.